Diferentes morfometricas por sexo de tres especies del genero opisthonema (Pisces: Clupeidae) de la costa del pacífico, Costa Rica - Víquez, Rigoberto (1990)
A biometric study conducted with the genus Opisthonema from the Pacific Coast of Costa Rica is presented. The research was done during 1985 and 1986. Three species: O. libertate, O.medirastre and O. bulleri, were sexually characterized using morphometric variables. Field date were used to elaborate a correlation matrix, and biometric indices were calculated as a function of total length. It was found that growh presented significant  differences between sexes and species.